2000
DOI: 10.1034/j.1600-0447.2000.102004265.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related change in personality disorder trait levels between early adolescence and adulthood: a community‐based longitudinal investigation

Abstract: PD traits tend to decline steadily in prevalence during adolescence and early adulthood. However, adolescents with PDs often have elevated PD traits as young adults, and the stability of PD traits appears to be similar during adolescence and early adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
214
5
16

Year Published

2001
2001
2016
2016

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 281 publications
(265 citation statements)
references
References 25 publications
27
214
5
16
Order By: Relevance
“…The sample prevalence of significant borderline features was 2.2 % in The Netherlands, 4.0 % in Belgium and 5.3 % in Australia, while a BPD diagnosis was suggested for 0.03 % in The Netherlands, 0.1 % in Belgium and 0.7 % in Australia. The somewhat higher prevalence in Australia could be due to the younger age range of the Australian sample as the prevalence rates of BPD are known to be highest among young adults (Paris et al 1987 ;Stone, 1990 ;Bernstein et al 1996 ;APA, 2000 ;Johnson et al 2000 ;Samuels et al 2002 ;Coid et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The sample prevalence of significant borderline features was 2.2 % in The Netherlands, 4.0 % in Belgium and 5.3 % in Australia, while a BPD diagnosis was suggested for 0.03 % in The Netherlands, 0.1 % in Belgium and 0.7 % in Australia. The somewhat higher prevalence in Australia could be due to the younger age range of the Australian sample as the prevalence rates of BPD are known to be highest among young adults (Paris et al 1987 ;Stone, 1990 ;Bernstein et al 1996 ;APA, 2000 ;Johnson et al 2000 ;Samuels et al 2002 ;Coid et al 2006).…”
Section: Resultsmentioning
confidence: 99%
“…This traditional view of personality disorder as a stable form of psychopathology has been held despite follow-up studies that reveal that only about 50% of patients will retain a PD diagnosis over time (Perry, 1993;McDavid & Pilkonis, 1996 ;Grilo et al 1998). Although many of these studies had design limitations, even recent methodologically rigorous follow-along studies have found that personality psychopathology decreases over time (Lenzenweger, 1999 ;Johnson et al 2000) and that a majority of patients do not stay consistently above diagnostic thresholds over periods as short as 1 or 2 years Grilo et al in press). The observed instability of PD diagnoses raises the obvious question of what is stable about a personality disorder, and might account for the commonly held belief that PDs persist ?…”
Section: Introductionmentioning
confidence: 99%
“…B. Johnson et al 2000Johnson et al , 2008 Benecke et al 2008;Highfield et al 2010;Kämmerer 2010;Kashdan et al 2013;Leising et al 2004;Myin-Germeys et al 2003;Yuan und Kring 2009).…”
Section: Der Verlauf Psychischer Störung Von Adoleszenz Ins Erwachsenunclassified